The Role of Education & Training Accounting in the transformation to International Accounting Standards in Iraqi Commercial Banks (Journal of Accounting and Financial Studies ( JAFS ), 2018)
That the international circumstances pressed towards the unification of the accounting practice and frame of mind, However , the political systems variation led to the difficulty of the application, It was resorting to study some of the requirements that contribute to the preparation of the local environment to be compatible with international accounting standards. Given the importance of education and training of accounting and its role in the process of transition to international accounting standards in the countries of the world, including Iraq, in particular the education and training of the leading accounting the transformation requirements human cadres working in the Iraqi commercial banks. The research aims to indicate the role of education and training of accounting in the rehabilitation and development of cadres working in the Iraqi position on the application of international accounting standards banks. Highlights have been reached and (that the development and rehabilitation of human capacity building is essential to the success of the application of international accounting standards in the commercial banks and to achieve the goal of attracting foreign investment